Automatic spatial gain control for an informed spatial filter - Braun, Sebastian; Thiergart, Oliver; Habets, Emanuel (International Conference on Acoustics, Speech and Signal Processing (ICASSP), 2014)
When capturing speech in a multi-talker telecommunication scenario, it is desirable to keep the enhanced signal at an equal loudness level for each speaker. Single-channel automatic gain control systems are not able to adjust the level of different talkers when they are simultaneously active. In this work, an automatic spatial gain control (ASGC) algorithm is proposed that adjusts the directional response of an existing informed spatial filter such that the direct sound of multiple sources can be kept at a constant desired loudness level at the output. The spatial filter additionally reduces diffuse sound and ambient noise. It is shown that the proposed AGSC works well within the tested scenario, and is able to adjust the levels of different speakers even during double talk scenarios.